Leadership Transformation Through Four Pillars of Shared Vision in Building a Learning Organization: A Case Study of Yayasan Imam Nawawi - Kemal Muhammad Rasyid; Rivan Syahrul Falah; Pratondo Ario Seno Sudiro; Robinson Situmorang; Muhammad Japar (UIN Sultan Aji Muhammad Idris Samarinda, 2026)
This study aims to analyze the implementation of shared vision as one of the core disciplines in building a learning organization at the Yayasan Dakwah Imam Nawawi. Using a qualitative case study approach, this study explores the four pillars of the vision developed by the foundation: Mission, Islamic Vision, Institutional Vision 2030, and Institutional Vision 2045. Data were collected through in-depth interviews with managers and directors of educational units and document analysis. The results show that segmenting the shared vision into four pillars helps management translate abstract values ”‹”‹into concrete strategic steps. Vision 2030 acts as a milestone, encouraging a culture of innovation, quality standards, and efficiency in resource use towards the grand vision of 2045. Vision 2045 becomes a long-term motivational driver towards global recognition. The implementation of these four pillars has been proven to transform the leadership pattern into a participatory and transformative one. The main challenges found are in aligning work patterns between supporting divisions and the education directorate, determining priorities for procurement of infrastructure and human resources, and the speed of communication and execution. This study sharpens Senge's (2006) Shared Vision theory by introducing the Layered Shared Vision approach. While vision is often perceived as a single, distant entity, this study demonstrates that dividing a vision into milestones and outcomes can mitigate the risk of the vision fading or losing relevance in the eyes of organizational members. The development of this layered, shared vision can be applied to similar educational institutions to ensure their survival and growth in the VUCA era. Keywords: Islamic Education Management, Learning Organization, Shared Vision, Yayasan Dakwah Imam Nawawi.